A population of highly energetic transient events in the centres of active galaxies. (December 2017) - Kankare, E.; Kotak, R.; Mattila, S.; Lundqvist, P.; Ward, M.; Fraser, M.; Lawrence, A.; Smartt, S.; Meikle, W.; Bruce, A.; Harmanen, J.; Hutton, S.; et al.
Abstract Recent all-sky surveys have led to the discovery of new types of transients. These include stars disrupted by the central supermassive black hole, and supernovae that are 10–100 times more energetic than typical ones. However, the nature of even more energetic transients that apparently occur in the innermost regions of their host galaxies is hotly debated1–3 . Here we report the discovery of the most energetic of these to date: PS1-10adi, with a total radiated energy of 2.3 × 1052 erg. The slow evolution of its light curve and persistently narrow spectral lines over ∼ 3 yr are inconsistent with known types of recurring black hole variability. The observed properties imply powering by shock interaction between expanding material and large quantities of surrounding dense matter. Plausible sources of this expanding material are a star that has been tidally disrupted by the central black hole, or a supernova. Both could satisfy the energy budget. For the former, we would be forced to invoke a new and hitherto unseen variant of a tidally disrupted star, while a supernova origin relies principally on environmental effects resulting from its nuclear location. Remarkably, we also discover that PS1-10adi is not an isolated case. We therefore surmise that this new population of transients has previously been overlooked due to incorrect association with underlying central black hole activity. The discovery of the most energetic transient event to date is reported. Its spectroscopic properties and temporal evolution imply it is powered by shock interaction between expanding material and large quantities of surrounding dense matter.